Cardiovascular outcomes of concurrent TAVR and PCI compared to TAVR alone using the U.S. national inpatient sample: 2011–2014. (25th November 2020) - Byer, M; Celli, D; Zarrabian, B; Colombo, R
Abstract: Introduction: The high concurrent prevalence of coronary artery disease (CAD) in patients with severe aortic stenosis (AS) inevitably forces experts to face a pressing decision whether to revascularize and replace the aortic valve at the same time. While current recommendations support combined transaortic valve replacement (TAVR) and percutaneous coronary intervention (PCI) for treatment of ostial/proximal lesions, or in unstable patients, less clear indications exist for patients not fulfilling this pattern. The population undergoing concomitant TAVR and PCI can be clinically challenging and thus it is important to further characterize prognosis and major cardiovascular outcomes in this cohort. Purpose: To assess the likelihood of major cardiovascular events in patients undergoing TAVR with PCI during the same hospital admission compared to those with TAVR only. As well as to have a better understanding of the risks and possible benefits of a combined procedure and thus aid in clinical decision-making. Methods: This study used the National Inpatient Sample (NIS) of patients undergoing a TAVR from 2011 to 2014. The NIS is a stratified systematic random sample of 20% hospital admissions in the United States. Internal Classification of Diseases Ninth Revision-Clinical Modification procedure codes were used to identify all patients that underwent a PCI and/or TAVR during the same admission. Patients aged greater than 50 years were included. Outcomes of interest included all-cause in-hospital mortality, new TIA/ischemic stroke, cardiogenic shock, cardiac arrest, hemopericardium, and length of stay. Multivariate logistic regression was used to adjust for patient and procedural confounders. Results: Among the 33, 652 patients who underwent TAVR between 2011 and 2014, 1, 179 underwent a PCI during the same hospital admission. The adjusted odds of all-cause in-hospital mortality was 3.05 (95% CI 1.95–4.75) in those with a TAVR+PCI compared to TAVR only. The adjusted odds of cardiac arrest and cardiogenic shock was 2.50 (95% CI: 1.48–4.22) and 4.85 (95% CI 3.05–7.7), respectively. Furthermore, the odds of a new TIA/ischemic stroke during the same admission was 0.86 (95% CI 0.35–2.07) and odds of hemopericardium was 3.13 (95% CI: 0.71–13.70). Conclusion: Concomitant PCI and TAVR during the same hospitalization was associated with higher all-cause in-hospital mortality, increased length of stay, cardiogenic shock, and cardiac arrest but does not appear to increase the likelihood of stroke/TIA. While this suggest worse outcomes in the cohort undergoing both procedures, the initial indications for these patients to receive a PCI might predispose them to these outcomes. Funding Acknowledgement: Type of funding source: None